Como escutar o corpo que dói?: reflexões sobre acontecimento de corpo e transferência - Nobrega, Pauleska Asevedo (2014)
From the place of psychoanalysis applied, with practice in the Department of Psychology from an Institution that offers ambulatory care by the Sistema Único de Saúde - SUS, we ask ourselves about how to listen to the body that hurts, crossed by a transfer that is not addressed to the analyst in an institutional context. In this clinic, the fixity of the discourse in bodily complains, constitutes resistance to interpret or insert enigmas, to the entrance of the other in the discourse, making the transference relationship a questiono We distinguish two fields in our experience: the analyst's work, to shudder what is fixed and, the side of the patient, to seek and remain in the medical-scientific discourse, leaving no gap. Through the field of language, what is disintegrated in the institutional body, is able to get presentified in the patient's body, under transfer. Our purpose in this research, is to discuss fibromyalgia and its relationship to science, underscoring the apogee of the bodies today, and contextualizing it in the viewer of psychoanalysis, to problematize and contextualize next, the genealogy of listening to the body that hurts in psychoanalytic theory. We used the resources of methodological research in psychoanalysis, based on interpretation and transfer, making reference to clinical case reports from the records served in the Department of Psychology of the Institution. We observe that teamwork can be the cause of change to the view ofthe health professional, that usually make appointments only from the medical classification, avoiding the unconscious gain that the users ofthe service do, to keep up in their disease.